2017
DOI: 10.1371/journal.pone.0180323
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal differences in the testicular transcriptome profile of free-living European beavers (Castor fiber L.) determined by the RNA-Seq method

Abstract: The European beaver (Castor fiber L.) is an important free-living rodent that inhabits Eurasian temperate forests. Beavers are often referred to as ecosystem engineers because they create or change existing habitats, enhance biodiversity and prepare the environment for diverse plant and animal species. Beavers are protected in most European Union countries, but their genomic background remains unknown. In this study, gene expression patterns in beaver testes and the variations in genetic expression in breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
3
10
0
Order By: Relevance
“…In vitro, via GABA‐A receptor activation, GABA increased proliferation of TM3 mouse Leydig cell lines (Geigerseder, Doepner, Thalhammer, Krieger, & Mayerhofer, ). Overall, present RNA‐Seq‐revealed testicular gene expressions in buntings are consistent with those found in European beavers' testes demonstrating seasonal differences in DEGs involved in the signal transduction, DNA repair, steroidogenesis, Wnt signaling, and calcium ion transport pathways (Bogacka et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In vitro, via GABA‐A receptor activation, GABA increased proliferation of TM3 mouse Leydig cell lines (Geigerseder, Doepner, Thalhammer, Krieger, & Mayerhofer, ). Overall, present RNA‐Seq‐revealed testicular gene expressions in buntings are consistent with those found in European beavers' testes demonstrating seasonal differences in DEGs involved in the signal transduction, DNA repair, steroidogenesis, Wnt signaling, and calcium ion transport pathways (Bogacka et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…At the molecular level, Maywood et al () identified factors that are possibly involved in the transcriptional, translational, and posttranslational control of testicular functions in the photoperiodic Syrian hamster ( Mesocricetus auratus ). Seasonal differences in testicular gene expressions have also been reported in roe deer, Capreolus capreolus (Weyrich et al, ) and European beavers, Castor fiber (Bogacka et al, ).…”
Section: Introductionmentioning
confidence: 86%
“…The overall statistics of our assembly (N50, L50, contig length, number of contigs >1k) were similar to the results documented in de novo assembled transcriptomes of other mammals, such as the beaver ( Castor fiber L . ; testis; Bogacka et al., ), and the Nile grass rat ( Arvicanthis ansorgei ; retina; Liu et al., ). However, we had higher values compared with marsupials such as the long‐nosed bandicoot ( Perameles nasuta ; heart, liver, spleen and kidney; Morris et al., ) and the Virginia opossum Didelphis virginiana ; kidney; Eshbach et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The N50 length (2354 nt), average length (1649 nt) of transcripts, the GC content (46.9%) and number of contigs > 1K nt (69,114) indicate successful library construction and good sequencing quality of the C. fiber placental transcriptome. Analysis of beaver testes transcriptome permitted to de novo assembly 373 million of high-quality reads into 130,741 unigenes with an average length of 1369.3 nt, N50 value of 1734 and GC content of 46.51% (Bogacka et al 2017 ). Our results are very consistent with those obtained in beaver testes, besides the same species was examined, similar methods and parameters were used in both studies that makes the results fully comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only a de novo approach may be efficient for identification of placental spatio-temporal gene expression in the Eurasian beaver. Only a few studies have been performed with some beaver tissues (Bogacka et al 2017 ; Chojnowska et al 2017 ; Czerwinska et al 2017 ; Lipka et al 2017a , b ; Lok et al 2017 ), but none of them concern de novo characterization of the beaver placental transcriptome. Thus, the objective of this study was to identify and characterize the placental transcriptome of the C. fiber .…”
Section: Introductionmentioning
confidence: 99%